The Impact of Sustainability and Environmental Ethics in Product Marketing Campaigns: A Qualitative Study with a Sociological and Economic Approach - Mandung, Fitriani (Golden Ratio of Data in Summary, 2024)
This study aims to examine the impact of sustainability and environmental ethics on consumer loyalty, brand perception, and economic resilience within product marketing campaigns. Driven by the increasing consumer demand for ethical business practices, this research integrates sociological and economic perspectives to understand how sustainable marketing shapes consumer-brand relationships and offers competitive advantages. Employing a qualitative methodology based on a comprehensive literature review, the study synthesizes data from recent research to provide a nuanced analysis of the socio-economic implications of sustainable marketing. The findings reveal that sustainability-focused brands not only foster long-term consumer loyalty but also experience enhanced brand equity and profitability due to a stronger alignment with consumer values. Furthermore, the research highlights the importance of transparency, which reinforces consumer trust and solidifies brand credibility in markets sensitive to greenwashing concerns. The study underscores the Theory of Planned Behavior and Brand Equity Theory as foundational frameworks for interpreting consumer responses to ethical marketing. These insights contribute to both academic discussions and practical applications, providing a roadmap for brands to leverage sustainability as a core strategy. The research concludes that sustainable marketing is a transformative approach that fosters socio-economic resilience, positioning brands for sustained success in eco-conscious markets